Grain Sorghum Cost-Return Budget in South Central Kansas - Dumler, Troy J.; Shoup, Douglas; Martin, Kent L. (My University, 2010)
This publication projects a budget that reflects expected income and costs based on grain sorghum production in south central Kansas.
MF575_2010_11
Keywords: MF575; Economics; Crops; MF